Optimization of Performance Analysis of Dual Relay Assisted FSO/RF System in Communication and its Impact - Vijay Kumar Tonk, Dr. Pradeep Kumar Yadav (International Journal of Advanced Science and Technology, 2020)
This article examines the impact of radio frequency co-channel interference (ICC) on the performance of the FSO / RF system assisted by dual relay communication. “The channels of the FSO / RF system considered with targeting errors. This unifying performance analysis framework includes expressions in closed form for probability of interruption, average bit error rate (BER) and ergodic capacity. The analysis of the signal raised to interference plus noise (SINR) culminates in easy-to-calculate expressions of the probability of interruption and the BER. SNR values increase with an increase in both the number of secondary carriers and the resistance to fading. Based on the above, therefore, the use of multiple RF / FSO is recommended only when the search for higher performance / capacity exceeds its power penalty. For numerical evaluation, these power series were truncated to a finite number of terms and were used to verify the accuracy of the proposed results.”